Radiolabeling and biological characterization of TPGS-based nanomicelles by means of small animal imaging - Tesan, Fiorella Carla (2017)
Introduction In recent years, nanomedicines have raised as a powerful tool to improve prevention, diagnosis and treatment of different pathologies. Among the most well investigated biomaterials, D-α-tocopheryl polyethylene glycol succinate (also known as TPGS) has been on the spot for the last decade. We therefore designed a method to biologically characterize TPGS-based nanomicelles by labeling them with 99mTc. Methods Labeling process was performed by a direct method. The average hydrodynamic diameter of TPGS nanomicelles was measured by dynamic light scattering and radiochemical purity was assessed by thin layer chromatography. Imaging: a dynamic study was performed during the first hour post radioactive micelles administration in a gamma camera (TcO4− was also administered for comparative purposes). Then two static images were acquired in ventral position: 1 h and 12 h post injection. Blood pharmacokinetics of 99mTc-TPGS during 24 h was performed. Results Images revealed whole body biodistribution at an early and delayed time and semiquantification was performed in organs of interest (%Total counts: soft tissue 6.1 ± 0.5; 3.9 ± 0.1, Bone 1.2 ± 0.2; 1.0 ± 0.1, Heart 1.5 ± 0.6; 0.7 ± 0.3, Kidneys 16.6 ± 1.3; 26.5 ± 1.7, Liver 8.6 ± 1.1; 11.1 ± 0.1 for 1 and 12 h post injection respectively). Conclusion This work demonstrated that TPGS based nanomicelles are susceptible to be radiolabeled with 99mTc thus they can be used to perform imaging studies in animal models. Moreover radiolabeling of these delivery nano systems reveals their possibility to be used as diagnostic agents in the near future.